Bonet, J. L., Caamaño Domínguez, F., Gimeno Feliu, J. M., Quintero Olivares, G. y Sala, P. (2017). Servicios Públicos e Ideología: El Interés General en Juego. Barcelona: Profit Editorial (Revista de Gestión Pública, 2020)
sin resumen